Study on the influence of cementation sequence on the mechanical properties and microstructure of MICP-modified ili loess - Guangming Shi; Ai Zhang; Yuan Xue; Dejun Yang; Changjiang Zhou (PLoS ONE, 2026)
The loess widely distributed in the Ili River Valley in north-western China is prone to soil erosion and geological hazards due to its high collapsibility, high soluble salt content and loose structure. This study investigates the effectiveness of Microbial-Induced Calcium Carbonate Precipitation (MICP) technology in improving the mechanical properties of Ili loess, focusing on a comparison of the macroscopic and microscopic properties under three different treatment sequences: bacterial suspension followed by cementation solution, cementation solution followed by bacterial suspension, and simultaneous application of both solutions. The results indicate that the treatment sequence significantly influences the MICP improvement effect, with the simultaneous application method performing best. Its unconfined compressive strength (115.83 kPa) increased by approximately 59.77% compared to untreated samples, and cohesion increased by approximately 55.06%, whilst the change in internal friction angle was minimal (<0.92%). Microscopic analysis indicated that the simultaneous application method formed a continuous, dense cementation network, effectively filling voids and bridging particles; in contrast, stepwise treatment tended to result in uneven distribution of the cementation material. It should be noted that this study constitutes a preliminary exploration under laboratory conditions; before the proposed method for optimising the cementation sequence can be applied to actual engineering projects, further research is required into durability (dry-wet/freeze-thaw cycles), scale effects and field validation. This study provides a potential environmentally friendly technical approach for the improvement of Ili loess.